Lengger Art In Prapah Hamlet, Panty Village, Panty District, Jember Regency, 1980-1990 - Fauziah Vina Yulianti; Sumarjono Sumarjono; Rully Putri Nirmala Puji; Bambang Soepeno; Guruh Prasetyo; Jefri Rieski Triyanto (JURNAL HISTORICA, 2022)
This article discusses the Lengger art in Prapah Hamlet, Panti Village, Panting District, Jember Regency. This study discusses (1) How is the background of the formation of Lengger art in Prapah Hamlet, Panti Village, Panti District, Jember Regency. (2) What is the function of Lengger art on social values ​​in Prapah Hamlet, Panti Village, Panti District, Jember Regency in 1980-1990. The method used in this study is a historical research method that uses interviews and secondary sources using sources in the form of documents. The results of this study are Lengger Art is an art that comes from a journey or tirakat from a grandfather named Kek Mo. Lengger dance used to be a fertility ritual. That is, the show is held in relation to the expressions of hope and gratitude of the farmers for the results that have been achieved. Then besides being used as an expression of gratitude, this art is also used as mbarang art or busking which is used as a field to earn a living by the Lengger dancers who have social values ​​in terms of material values, vital values, and spiritual values. Keywords: Lengger Arts, Social Values, Prapah Village